The myth of the age of entitlement : millennials, austerity, and hope - Cairns, James Irvine, 1979- (2017)
"Drawing on interviews, economic data, and popular media, Cairns debunks the popular age of entitlement myth - where Millennials and Generation Y are accused of expecting good grades, top jobs, and exciting lifestyles without having to pay their dues. Instead, Cairns suggests that rather than being overly entitled, millennials are being dis-entitled on multiple fronts. Precarious employment, student debt, and global ecological disaster mark their present and future. The age of entitlement ignores this reality, but more importantly it undercuts the possibility that young people should be entitled to something better. It legitimizes austerity politics, demanding that people settle for less. The book explains that forms of "democratic entitlement" have driven struggles for social justice throughout history. In contrast to dominant depictions of Generation Y, the case studies show youth-led justice movements struggling for better jobs, more democratic education, and ecological sustainability. It concludes that forces of "oppressive entitlement" that dominate much of society today will be diminished only through the expansion of new democratic entitlements."--
The age of entitlement -- Democratic and oppressive entitlements -- Zeroed down : The flexible millennial worker -- Austerity U : Teaching and resisting disentitlement on campus -- Millennial blowout : Eco-disentitlement versus ecological justice -- Everything for everybody.
Includes bibliographical references (pages 165-183) and index.
Issued also in electronic formats.
Keywords: Generation Y -- Political activity; Young adults -- Political activity; Conflict of generations; Entitlement attitudes; Identity politics; Generation Y -- Social conditions; Young adults -- Social conditions -- 21st century